Pengembangan Proses Gerinda Silinder Permukaan Luar - Harbintoro, Sony; Sutisna, Agus; Pujiyanto, Pujiyanto; Hidayat, Sarip; Suherman, Agus (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
The abrasive machining process is called the grinding process using a wheel grinding. The process of abrasive machining is usually in the final stages of making a product or finishing product so that it becomes essential in making products because it determines the final quality of a product. The purpose of this research is to develop the external cylindrical grinding process in column products for one of the components for drilling machines by modifying the grinding process in the lathe machine. The study was conducted using a wheel head of tools sharpening machine that is mounted on a lathe machine. The stages of this research began with the lathe process. Then without removing the product from the lathe, the external surface cylindrical grinding process is carried out so that there is no need to be set up the workpiece because the central inertia axis of the workpiece has one axis with its geometric axis. The measurement results of the external surface cylindrical grinding process are carried out using a bird-cage strategy by dividing the measurement into six segments. From each segment, the data is collected at eight measuring points. Based on the measurement results, in sample no.3 in segments B and D there is an increase in measurement results, that is Â Ã˜ 100 + 0.018, but still below the maximum limit of Ã˜ 100 + 0.020.